Improved survival in critically injured combat casualties treated with fresh whole blood by forward surgical teams in Afghanistan. Issue Volume 60:Issue S3(2020) (3rd June 2020) - Gurney, Jennifer; Staudt, Amanda; Cap, Andrew; Shackelford, Stacy; Mann‐Salinas, Elizabeth; Le, Tuan; Nessen, Shawn; Spinella, Philip
Abstract : BACKGROUND: The objective of this study was to assess transfusion strategies and outcomes, stratified by the combat mortality index, of casualties treated by small surgical teams in Afghanistan. Resuscitation that included warm fresh whole blood (FWB) was compared to blood component resuscitation. STUDY DESIGN AND METHODS: Casualties treated by a Role 2 surgical team in Afghanistan from 2008 to 2014 who received 1 or more units of red blood cells (RBCs) or FWB were included. Patients were excluded if they had incomplete data or length of stay less than 30 minutes. Patients were separated into two groups: 1) received FWB and 2) did not receive FWB; moreover, both groups potentially received plasma, RBCs, and platelets. The analysis was stratified by critically versus noncritically injured patients using the prehospital combat mortality index. Kaplan‐Meier plot, log‐rank test, and multivariable Cox regression were performed to compare survival. RESULTS: In FWB patients, median units of FWB and total blood product were 4.0 (interquartile range [IQR], 2.0‐7.0) and 16.0 (IQR, 10.0‐28.0), respectively. The Kaplan‐Meier plot demonstrated that survival was similar between FWB (79.1%) and no‐FWB (74.5%) groups (p = 0.46); after stratifying patients by the combat mortality index, the risk of mortality was increased in the no‐FWB group (hazard ratio, 2.8; 95% confidence interval, 1.2‐6.4) compared to the FWB cohort. CONCLUSION: In forward‐deployed environments, where component products are limited, FWB has logistical advantages and was associated with reduced mortality in casualties with a critical combat mortality index. Additional analysis is needed to determine if these effects of FWB are appreciable in all trauma patients or just in those with severe physiologic derangement.